Relationship Between Tamsulosin Use and Surgical Complications of Cataract Surgery in Elderly Patients: Population-Based Cohort Study - Kwak, Jiehoon; Han, Jung Yeob; Moon, Su Young; Nam, Sanghyu; Kim, Jae Yong; Tchah, Hungwon; Lee, Hun (Frontiers in Medicine, 2022)
Purpose Although several previous studies have investigated the relationship between tamsulosin use and surgical complications of cataract surgery, no population-based cohort study has been conducted for the Asian population. We aimed to investigate the relationship between tamsulosin use and surgical complications of cataract surgery in the Korean elderly population. Methods This nationwide population-based retrospective cohort study included elderly patients (≥60 years) who had undergone cataract surgery in the period from 2003 to 2015. Baseline characteristics were age, sex, income, residence, and systemic, and ocular comorbidities (glaucoma, myopia, eye trauma, diabetes mellitus with ophthalmic manifestations, severe cataract, age-related macular degeneration). The exposure of interest was tamsulosin use within 1 year before cataract surgery. Logistic regression model was used to evaluate the relationship of tamsulosin use with surgical complications of cataract surgery. Results The rate of surgical complications of cataract surgery was 0.88% (375/42,539) in the non-tamsulosin group and 0.83% (71/8,510) in the tamsulosin group. The groups showed no significant difference in the risk of surgical complications of cataract surgery in the unadjusted model [odds ratio (OR) = 0.946; 95% confidence interval (CI):0.733–1.220; P = 0.669]. Additionally, tamsulosin use was not significantly associated with surgical complications of cataract surgery in the fully adjusted model accounting for age, income, residence, and systemic and ocular comorbidities (OR = 0.997; 95% CI: 0.749–1.325; P = 0.981). Conclusions The rate or risk of surgical complications of cataract surgery does not change with tamsulosin use. We suggest that better surgical techniques and surgeons' cognizance of the patient's tamsulosin use could improve surgical outcomes, without increasing surgical complications.